Embracing Cultural Threads: A Qualitative Exploration of English Language Teaching Materials Within an Intercultural Perspective in an Indonesian Multilingual Context - Billy Nathan Setiawan (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This study aimed to investigate the selection, adaptation and use of English language teaching and learning (ELTL) resources from an intercultural perspective (Liddicoat & Scarino, 2013) in order to provide greater sensitivity to the local context. In recent decades, scholars in the field have attempted to move towards the inclusion of local content in ELTL, including in Indonesia, in order to challenge the 'native speaker' paradigm, which has been criticized for lacking sensitivity to the local context. However, little research has been conducted to examine the role of resources in providing opportunities for intercultural interaction between students' own languages and cultures and English (as the target language and culture). A case study within a qualitative paradigm, involving document analysis and an in-depth teacher interview, was conducted at an international university in Indonesia. Thematic analysis of the data revealed that the selection, adaptation and use of resources that invited attentiveness to language and beyond, and that took into account students' 'lifeworlds' ('home cultures and languages, and the trajectory of experiences, interests, motivations and values developed from them' [Liddicoat & Scarino, 2013]), provided engagement and meaningfulness in ELTL in the local context. The study also showed that 'both the range of texts and what teachers do with them' (Kohler, 2020) were fundamental to providing meaningful ELTL experiences in the local context. AbstrakPenelitian ini bertujuan untuk menyelidiki pemilihan, adaptasi, dan penggunaan materi pengajaran dan pembelajaran bahasa Inggris (ELTL) dari perspektif lintas budaya (Liddicoat & Scarino, 2013) untuk memberikan kepekaan yang lebih besar terhadap konteks lokal. Dalam beberapa dekade terakhir, para ahli di bidang ini telah mencoba untuk bergerak menuju inklusi konten lokal dalam ELTL, termasuk di Indonesia, untuk menantang paradigma 'penutur asli', yang telah dikritik karena kurangnya kepekaan terhadap konteks lokal. Namun, hanya sedikit penelitian yang telah dilakukan untuk meneliti peran materi belajar mengajar dalam memberikan kesempatan untuk interaksi antarbudaya antara bahasa dan budaya siswa dan bahasa Inggris (sebagai bahasa dan budaya target). Sebuah studi kasus dalam paradigma kualitatif, yang melibatkan analisis dokumen dan wawancara mendalam dengan guru, dilakukan di sebuah universitas internasional di Indonesia. Analisis tematik terhadap data menunjukkan bahwa pemilihan, adaptasi, dan penggunaan materi belajar mengajar yang mengundang perhatian terhadap bahasa dan sekitarnya, serta mempertimbangkan 'dunia kehidupan' siswa ('budaya dan bahasa asal, serta lintasan pengalaman, minat, motivasi, dan nilai-nilai yang dikembangkan dari mereka' [Liddicoat & Scarino, 2013]), memberikan keterlibatan dan kebermaknaan dalam ELTL dalam konteks lokal. Studi ini juga menunjukkan bahwa 'baik ragam teks dan apa yang dilakukan guru dengan teks tersebut' (Kohler, 2020) merupakan hal yang mendasar dalam memberikan pengalaman ELTL yang bermakna dalam konteks lokal.